Hydrophobic multiscale cavities for high-performance and self-cleaning surface-enhanced Raman spectroscopy (SERS) sensing - Zhao, Xiaofei; Liu, Chundong; Yu, Jing; Li, Zhen; Liu, Lu; Li, Chonghui; Xu, Shicai; Li, Weifeng; Man, Baoyuan; Zhang, Chao (Nanophotonics (Berlin, Germany), 2020)
Cavity array, with excellent optical capture capability, has received increasing attention for the surface-enhanced Raman spectroscopy (SERS)-active substrates. Here, we proposed molybdenum disulfide (MoS ) nanocavities growing on pyramid Si (PSi) composed of in situ reduced Au nanoparticles (AuNPs), which can form the multiscale cavities (MSCs), and is facile for the couple of the plasmon. We demonstrated that the PSi/MoS /Au MSCs can serve as highly sensitive, uniform, and stable SERS substrates for rhodamine 6G (R6G), crystal violet, and adenosine triphosphate detection, benefiting from the synergistic effect of the enhanced light trapping and the effective plasmonic couple. The couple of the plasmon in the MSCs is evidently proved by finite-difference time domain simulation, showing the strong electromagnetic field is located around the cavity wall. Moreover, the excellent hydrophobicity of the PSi/MoS /AuNPs substrate endows it with the ability for the directional monitoring of organic pollutant in a mixture of oil and water. Finally, we demonstrated the MSCs with outstanding photocatalytic performance could achieve the renewable utilization by self-cleaning, which was attributed to the fast electron transfer and effective light absorption. The proposed PSi/MoS /AuNPs MSC represents a robust mean using the plasmonic metal/semiconductor heterostructure for high-performance SERS sensors and photodegradation.